Toward minimally invasive, continuous glucose monitoring in vivo - Vrančić, Christian; Gretz, Norbert; Kröger-Lui, Niels; Neudecker, Sabine; Pucci, Annemarie; Petrich, Wolfgang (Biomedical vibrational spectroscopy V, 2012)
Diabetes mellitus is a disorder of glucose metabolism and it is one of the most challenging diseases, both from a medical and economic perspective. People with diabetes can benefit from a frequent or even continuous monitoring of their blood glucose concentrations. The approach presented here takes advantage of the observational nature of biomedical vibrational spectroscopy in contrast to chemical reactions which consume glucose. The particular technique employed here is based on the high sensitivity of mid-infrared transmission spectroscopy where strong vibrational bands of glucose can be monitored at wavelengths around 10 μm. The strong absorption of water in this spectral region was mitigated by the use of quantum cascade lasers and very short interaction path lengths below 50 μm. Various sensor concepts have been explored. In one of the concepts, the interaction of mid-infrared radiation with glucose is established within a miniature measurement cavity, formed by a gap between two silver halide fibers. In recent experiments, an additional quantum cascade laser was used for reference purposes. The long-term drift could significantly be reduced for time intervals > 1000 s, e. g., by more than 60% for a 3 hour interval. This extension for the compensation of long-term drifts of the measurement system in vitro is an important contribution towards the applicability in vivo.